Synonymy in the Semio-thematic Group "Clothing" - Ghamoyan, Lusine (Bulletin of Yerevan University B: Philology, 2021)
The synonymous words of the semio-thematic group "clothing" appear in the language in different ways. Synonymous series can be composed of two versions of literary language, dialects, Grabarian և Middle Armenian words, neo-formations, etc. These synonyms are classified and grouped according to different criteria. The most important of them is the semantic criterion, which determines the degree of semantic similarity or generality of these words, as well as the difference. Taking into account the period when these synonyms are used, we distinguish two groups of synonyms denoting the concept of "clothing": synchronic and diachronic. The parts of the synonym series belong to different parts of speech, have different word-formation patterns, and quantitatively they have two and multiple parts. The role of synonyms in the semantic field "clothing" is huge in the process of enrichment of the language vocabulary and stylistic means, development of speech culture.